Evaluating the influence of land use, landscape properties, precipitation and fish on aquatic ecosystem functioning and biodiversity through large temporal and spatial scale assessments across lakes and reservoirs - Nobre, Regina Lúcia Guimarães (2020)
Nutrient cycling is a fundamental ecosystem service as it provides an adequate balance of elements that are necessary for life. In freshwaters, the balance of nitrogen (N) and phosphorus (P) are of special interest as they often limit or control primary production and biomass formation. While the availability of these nutrients is fundamental for the maintenance of biodiversity and productivity of freshwaters, their excess can lead to eutrophic conditions that are associated with impaired water quality and biodiversity loss. The nutrient balance in freshwaters can potentially be affected by a variety of biotic and abiotic, external and internal pathways. In this thesis, two frameworks were explored. First, a spatial framework focused on external processes, where we investigated the direct and indirect effects that land use (i.e. type, extent), precipitation and landscape properties (i.e. lake origin, lake and catchment absolute and relative size and geomorphology) have on biotic and abiotic properties of freshwater systems. More specifically, in chapter one we evaluated, across 98 tropical lakes and reservoirs, the individual and interactive effects of land use, precipitation and landscape properties on patterns of water quality parameters (N, P and chlorophyll-a). In chapter two, we characterized the 98 lakes as natural or artificial and compared them regarding the landscape properties of their surroundings, their morphometry, and their physico/chemical characteristics to verify whether those factors can be associated with average patterns of phytoplankton community structure at both local and regional scales. The second approach, presented in Chapter 3, was a long-term temporal framework focused on internal processes related to nutrient cycling where we assessed whether an omnivorous fish with high biomass and growth rate is a source or sink of N and P to the pelagic zone of a temperate eutrophic lake, at various time scales ranging from days to 20 years.